Gastric roof and cardiac cancer - Bergalli, Luis; Aliano, Artigas; Balboa, Oscar; Estapé, Gonzalo; Musse, Ignacio; Soto, José; Verccelli, Jorge (Cirugía del Uruguay, 1979)
Current information on carcinoma of proximal gastrie third does not present any significant histopathologic differences with that affecting other parts of the organ. Its histogenesis is the result of a series of lesions, such as intestinal metaplasia, and the variety of gastric polyps known as papillary adenomas; these are rare but novertheless entail considerable diagnostical problems.